2001
DOI: 10.1006/jtbi.2001.2415
|View full text |Cite
|
Sign up to set email alerts
|

Can Diving-induced Tissue Nitrogen Supersaturation Increase the Chance of Acoustically Driven Bubble Growth in Marine Mammals?

Abstract: The potential for acoustically mediated causes of stranding in cetaceans (whales and dolphins) is of increasing concern given recent stranding events associated with anthropogenic acoustic activity. We examine a potentially debilitating non-auditory mechanism called rectified diffusion. Rectified diffusion causes gas bubble growth, which in an insonified animal may produce emboli, tissue separation and high, localized pressure in nervous tissue. Using the results of a dolphin dive study and a model of rectifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 35 publications
3
90
0
Order By: Relevance
“…Modelling efforts on diving mammals, on the other hand, have reported divergent results when investigating the effect that changes in ascent rate has on tissue and blood P N 2 (Houser et al, 2001;Fahlman et al, 2006Fahlman et al, , 2007Zimmer and Tyack, 2007). Fahlman et al (2006) suggested that a reduction in the ascent coupled with an increase in tot Q  close to the surface could reduce Pv N 2 by as much as 45%.…”
Section: Ascent Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Modelling efforts on diving mammals, on the other hand, have reported divergent results when investigating the effect that changes in ascent rate has on tissue and blood P N 2 (Houser et al, 2001;Fahlman et al, 2006Fahlman et al, , 2007Zimmer and Tyack, 2007). Fahlman et al (2006) suggested that a reduction in the ascent coupled with an increase in tot Q  close to the surface could reduce Pv N 2 by as much as 45%.…”
Section: Ascent Ratementioning
confidence: 99%
“…Houser et al (2001) used the results published by Ridgway and Howard (1979) in a theoretical model based on gas diffusion to show that beaked whale diving patterns (based on simulated dive data) could lead to chronic tissue accumulation of N 2 gas. Their simulations illustrated the potential increase in N 2 caused by relatively shallow (100 m, 9 min) dives with short (1 min) surface intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of high-intensity anthropogenic sounds, particularly midfrequency (2-4·kHz) sonar, has been associated with mass strandings of Cuvier's beaked whales (Evans and England, 2001;Frantzis, 1998;Simmonds and Lopez-Jurado, 1991). Physiological mechanisms including rectified diffusion of gas bubbles in tissues (Crum and Mao, 1996;Houser et al, 2001), gas emboli formation in body fats (Jepson et al, 2003;Fernandez et al, 2004) or bubble or lung resonance (Finneran, 2003) may explain the observed hemorrhaging in the lungs, acoustic pathways, brain, spinal cord, kidneys and eyes, congestion and bubbles in the brain, and embolisms in body fats in stranded animals (Evans and England, 2001;Fernandez et al, 2004). The role that sound exposure played in these strandings and subsequent deaths remains controversial.…”
mentioning
confidence: 99%
“…Whales typically balance dives to manage nitrogen bubble formation; a sound stimulus may disrupt the animals' normal dive regime (Houser et al 2001). A sudden change in air pressure allows the formation of in vivo nitrogen bubbles that can migrate into the circulatory system, causing tissue damage (Southall et al 2007).…”
Section: Potential Lethal Effectsmentioning
confidence: 99%